Energy and flux measurement of the neutrons produced in a gas cell - Doukellis, G.; Paradellis, T.; Kossionides, S. (HNPS Advances in Nuclear Physics, 2019)
The neutron flux and energy distribution of the neutrons produced in a gas cell were measured using a silicon semiconductor detector. The energy spectra produced by the borbardment of the silicon detector with neutrons were simulated using Monte Carlo techniques and were compared with the measured spectra